199k views
1 vote
Simplify the expression 2(w+7)+6(3w−1).

2 Answers

5 votes

Answer:

4 • (5w + 2)

Explanation:

STEP

1

:

Equation at the end of step 1

(2 • (w + 7)) + 6 • (3w - 1)

STEP

2

:

Equation at the end of step 2

2 • (w + 7) + 6 • (3w - 1)

STEP

3

:

STEP

4

:

Pulling out like terms

4.1 Pull out like factors :

20w + 8 = 4 • (5w + 2)

User Jeyhun Karimov
by
5.8k points
7 votes

Answer:

20w + 8

Explanation:

2(w+7)+6(3w−1).

step 1 distribute the 2 to the w and the 7

2 * w = 2w

2 * 7 = 14

we now have 2w + 14 + 6( 3w - 1 )

step 2 distribute the 6 to the 3w and -1

6 * 3w = 18w

6 * -1 = -6

we now have 2w + 14 + 18w - 6

step 3 combine like terms

2w + 18w = 20w

14 - 6 = 8

we're left with 20w + 8

User Marjan Moderc
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.